Characterization of starch structures isolated from the grains of waxy, sweet, and hybrid sorghum (Sorghum bicolor L. Moench) - Kang, Xuemin; Zhu, Wentao; Xu, Tongcheng; Sui, Jie; Gao, Wei; Liu, Zhiquan; Jing, Haichun; Cui, Bo; Qiao, Xuguang; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
In this study, starches were isolated from inbred (sweet and waxy) and hybrid (sweet and waxy) sorghum grains. Structural and property differences between (inbred and hybrid) sweet and waxy sorghum starches were evaluated and discussed. The intermediate fraction and amylose content present in hybrid sweet starch were lower than those in inbred sweet starch, while the opposite trend occurred with waxy starch. Furthermore, there was a higher A chain (30.93–35.73% waxy, 13.73–31.81% sweet) and lower B2 + B3 chain (18.04–16.56% waxy, 24.07–17.43% sweet) of amylopectin in hybrid sorghum starch. X-ray diffraction (XRD) and Fourier transform infrared reflection measurements affirm the relative crystalline and ordered structures of both varieties as follows: inbred waxy > hybrid waxy > hybrid sweet > inbred sweet. Small angle X-ray scattering and 13C CP/MAS nuclear magnetic resonance proved that the amylopectin content of waxy starch was positively correlated with lamellar ordering. In contrast, an opposite trend was observed in sweet sorghum starch due to its long B2 + B3 chain content. Furthermore, the relationship between starch granule structure and function was also concluded. These findings could provide a basic theory for the accurate application of existing sorghum varieties precisely.